Efficacy Of Drumstick (Moringa Oleifera) Leaf-Water Extract On The Modulation Of Oxidative Stress Through Expression Of Superoxide Dismutase And Catalase Genes In High Fat Fed Rats (Applied Biological Research, 2019)
Obesity-related kidney diseases require an effective approach to avert high fat-diet induced renal damage through oxidative stress. The aim  of present study was to evaluate antioxidative strength and protective  effects of drumstick (Moringa oleifera) leaf-water extract (DLWE) on  kidney in Wistar rats. In this study rats were either fed with control  diet or control diet with DLWE or high-fat diet or high-fat diet with  DLWE for 16 weeks. The body and kidney weight, oxidative status  (lipid peroxidation, ferric reducing antioxidant power, non-enzymatic  and enzymatic antioxidants) and gene expression of superoxide  dismutase and catalase were assessed. High fat-diet fed rats showed changes in body and kidney weights, increase in lipid peroxidation and  decrease in ferric reducing antioxidant power, vitamin C, glutathione,  superoxide dismutase and catalase indicating a higher oxidative stress  index. At molecular level, high fat-diet caused a significant reduction  in gene expression of superoxide dismutase and catalase which was  overcome by DLWE supplementation. The oral supplementation of  DLWE restored oxidative stress in high fat-diet fed rats. The diet  restored lipid peroxidation and kidney antioxidants to control group level. It seems that DLWE has therapeutic potential, so be developed  as a supplement to prevent obesity and related oxidative stress.
Keywords: Antioxidant; drumstick; gene expression; obesity; oxidative stress